(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
TORCH infections—namely toxoplasmosis (Toxoplasma gondii), cytomegalovirus (CMV) infection, rubella virus infection, herpes simplex virus (HSV) infection, and other vertically transmitted infectious agents—are of major importance in prenatal diagnostics. This study compares widely used serological methods (detection of IgG/IgM antibodies, IgG avidity testing, etc.) and molecular methods (PCR, real-time PCR, nested PCR, LAMP, etc.) for the detection of TORCH complex pathogens. The article discusses the sensitivity, specificity, practical convenience, cost, and suitability of both approaches for laboratory practice. Based on statistical literature, it is concluded that molecular methods show superiority over serological methods in certain cases; however, since serology is still widely used, the need for integrated diagnostic models is emphasized. This analysis highlights future perspectives for TORCH diagnostics in prenatal screening and neonatology.